Aplication of Photosynthetic bacteria and Various NAA (Naphthalene 1-Acetid Acid) Concentration on the Growth of Vanilla Cuttings (Vanilla planifolia Andrews.) - Dian Nugroho (PT FORMOSA CENDEKIA GLOBAL, 2023)
Vanilla is one of the spice plants that has the potential to be developed in Indonesia because its selling price is high. In the cultivation process, the main obstacle that is often experienced is the problem of seed quality. This research aims to determine the best time to apply PSB and NAA concentration for the growth of vanilla cuttings. This research was a split plot design with 2 levels of factors, namely time of administration of PSB (without, once a week, and once every 2 weeks) and NAA concentration (100 ppm, 150 ppm, and 200 ppm). The observation results were analyzed using ANOVA with a 5% significance level followed by DMRT with a 95% confidence level. There is an interaction between the parameters of the day the shoots emerge and the dry weight of the roots. PSB application treatment once a week gives the best results in most parameters. NAA concentration level treatment gave equally good results.